2018
DOI: 10.1038/s41598-017-18946-y
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-phosphate complex increased during subchondral bone remodeling affects earlystage osteoarthritis

Abstract: An activation of osteoclasts and subchondral bone remodeling is a major histologic feature of early-stage osteoarthritis (OA), which can be accompanied by an increase of calcium (Ca) and phosphate (Pi) level in the subchondral milieu. Considering articular cartilage gets most of nutrition from subchondral bone by diffusion, these micro-environmental changes in subchondral bone can affect the physiology of articular chondrocytes. Here, we have shown that Ca is increased and co-localized with Pi in articular car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Next, we tested if the breakdown products of chondroitin-sulfate can function as damage-associated molecular patterns (DAMPs) that can be responsible for the increase of proteases and oxidative stress. In the preceding study, we confirmed that the ligands for TLR2 and TLR4 significantly involves in the expression of MMP-3 and MMP-13 in chondrocytes 21 . On this basis, we inhibited the function of TLR2 and TLR4 with OxPAPC, a dual TLR2 and TLR4 inhibitor or LPS-RS, a functional TLR4 inhibitor through MD2 inhibition, and assessed the chondrocyte phenotype by chondroitinase treatment.…”
Section: Resultssupporting
confidence: 78%
“…Next, we tested if the breakdown products of chondroitin-sulfate can function as damage-associated molecular patterns (DAMPs) that can be responsible for the increase of proteases and oxidative stress. In the preceding study, we confirmed that the ligands for TLR2 and TLR4 significantly involves in the expression of MMP-3 and MMP-13 in chondrocytes 21 . On this basis, we inhibited the function of TLR2 and TLR4 with OxPAPC, a dual TLR2 and TLR4 inhibitor or LPS-RS, a functional TLR4 inhibitor through MD2 inhibition, and assessed the chondrocyte phenotype by chondroitinase treatment.…”
Section: Resultssupporting
confidence: 78%
“…1 ). The activation of osteoclasts in the early stage of OA induces active remodelling of subchondral bone 12 , 18 . This process can release matrix-derived coupling factors, such as Insulin-like growth factor 1 (IGF-1) and TGFβ, and the inhibition of TGFβ in subchondral bone can attenuate the progression of surgically induced OA 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a possible explanation for the catabolic function of TGFβ via TG2 in subchondral bone. Active subchondral bone remodelling during early OA can increase both TGFβ and calcium levels in the subchondral milieu 12 . TGFβ can increase the expression of TG2 in hypertrophic chondrocytes in the neighbouring subchondral bone 9 , and this calcium-rich environment in subchondral bone may enhance the calcium-dependent enzyme activity of TG2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations